Evaluation of the FERA study on bumble bees and consideration of its potential impact on the EFSA conclusions on neonicotinoids - European Food Safety Authority (EFSA Journal, 2013)
The European Food Safety Authority was requested to clarify whether the new publication on the effects of neonicotinoid seed treatments on bumble bee colonies under field conditions (March, 2013; Thompson et al.) has an impact on the EFSA Conclusions on the three neonicotinoids clothianidin, thiamethoxam and imidacloprid (EFSA Journal 2013;11(1):3066; EFSA Journal 2013;11(1):3067; EFSA Journal 2013;11(1):3068). The Conclusions on neonicotinoids, published on 16 January 2013, did not permit to perform a risk assessment for bumble bees and identified the need for further information to address the risk to pollinators other than honey bees. The conclusions of this scientific statement were reached on the basis of the evaluation of the study report by Thompson et al. (2013),and additional raw data made available by the study authors to EFSA. The study investigated the exposure of bumble bee colonies placed in the vicinity of crops treated with neonicotinoids and its major effects on bumble bee colonies. The current assessment concluded that, due to the weaknesses of the study design and methodology, the study did not allow to draw any conclusion on the effects of neonicotinoids on exposed bumble bee colonies, and confirmed that the outcome of the conclusions drawn for the three neonicotinoid insecticides remains unchanged.